Peran Instagram @officialpersebaya dalam Membranding Pemain Sepak Bola Muda di Klub Persebaya Surabaya - Wahyuadji, Haryo Ontowiryo; Anita Agustina Wulandari (LPPM Stikosa-AWS, 2024)
This research aims to find out the role of Instagram @officialpersebaya in comparing young football players at the Persebaya Surabaya Club, with a focus on applying the principles of Specialization, Difference, Appearance and Firmness by the Instagram account @officialpersebaya. This study analyzes how these accounts leverage various social media features to highlight young players' unique talents and potential, build a positive image, and strengthen fan engagement. The research method used involves observing the @officialpersebaya account which includes match highlights, training videos and player achievements in various competitions. This study also evaluates the use of Instagram features such as Stories, Reels, and Live in promoting and showcasing the development of young players. The research results show that a consistent and targeted personal branding strategy not only increases the visibility and reputation of young players but also strengthens the club's image as a developer of quality talent. The research results show that a consistent and targeted personal branding strategy not only increases the visibility and reputation of young players but also strengthen the club's image as a developer of quality talent. The @officialpersebaya account applies personal branding theory (relevance) so that in every content posted, be it photos, reels or insta stories, there is an effort to provide information that is relevant to the needs and interests of its followers.